Robert Bohn & Michael Engelbrecht, Hg.: Weltgeltung und Regionalitdt. Nordeuropa um 1900. Studia septemtrionalia, Band 1, Hg. Hain Rebas. (Peter Lang, Frankfurt am Main 1992). 314 s. - Lyke Christensen, Christa (Historie/Jyske Samlinger, 1994)
-